Idle Hands Are Not the Devil’s Playthings - Paterson, Alex (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
This paper extends upon Costica Bradatan’s analysis of Emil Cioran in his book, In Praise of Failure. It provides a defence of Cioran’s lifestyle - his refusal to engage in traditional concepts of work and his ideal of ’doing nothing’. I defend Cioran in three ways. First, I argue that Cioran’s mantra of doing nothing enabled him to contemplate, to come closer to the absolute, and to contribute to the cultivation of civilisation through his thought. Second, I argue that Cioran’s lifestyle enabled him to extricate himself from the damaging cycle of success and failure. By settling for failure from the very beginning, Cioran was able to live without the distractions and damages caused by fear of failure and desire for recognition or success. Third, I argue that Cioran’s lifestyle is a radical expression of authenticity and freedom.